2013
DOI: 10.1542/peds.2012-3986
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 Supplementation and Childhood Diarrhea: A Randomized Controlled Trial

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Hypovitaminosis D is common among children. Although there is prolific biochemical literature linking vitamin D to enteric immunologic function, there is a paucity of prospective data exploring the role of supplementation in prevention of diarrheal illnesses. WHAT THIS STUDY ADDS:In a high-risk population, quarterly supplementation with 100 000 IU of vitamin D 3 did not reduce the risk for first or recurrent diarrheal illnesses in a population of children aged 1 to 29 months in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 34 publications
(12 reference statements)
0
27
1
5
Order By: Relevance
“…Another randomized controlled trial with 3-monthly bolus supplementation with 100,000 IU of vitamin D3 among children aged 1 to 29 months, showed no effect on the risk of diarrheal illnesses [41]. The finding of this study underscores the need for further research to explore vitamin D serologic levels in relation to immune function and physiologic responses to gut infections.…”
Section: Discussionmentioning
confidence: 66%
“…Another randomized controlled trial with 3-monthly bolus supplementation with 100,000 IU of vitamin D3 among children aged 1 to 29 months, showed no effect on the risk of diarrheal illnesses [41]. The finding of this study underscores the need for further research to explore vitamin D serologic levels in relation to immune function and physiologic responses to gut infections.…”
Section: Discussionmentioning
confidence: 66%
“…A randomized controlled trial with 3-monthly bolus supplementation with 100,000 IU of vitamin D3 among children aged 1 to 29 months, showed no effect on diarrheal illnesses [47]. Our study was done in urban slum where constant exposure to pathogenic organisms and subsequent enteric infection is common in children [48].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recently conducted randomised controlled trial with quarterly bolus dose of vitamin-D at high-risk population aged 1-29 months did not find any effect on first or recurrent incidence of diarrhoea. 13 In a longitudinal study, among school-going children (mean age 8.9 years) in Colombia, it was found that vitamin-D-deficient children were at greater risk of gastrointestinal illness. 12 Our study consisted of children 6-24 months of age living in urban slums, where the burden of disease is highest because of poor sanitation and socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Probably for this reason, our study findings were concordant with the finding of randomised controlled trial with vitamin-D supplementation conducted in a similar setting like in Afghanistan. 13 Population-based studies conducted to determine the effect of serum retinol or zinc in incidence and severity of childhood diarrhoea did not consider the nutritional status of children nor targeted the population most at risk, especially undernourished children. 4,5 To that extent, our finding that normal-weight children with insufficient serum zinc had an increased incidence and severity of diarrhoea compared with children with sufficient serum zinc status is a novel finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation